Effectiveness on the Use of Blended Learning Approach (BLA): Its Implications on the Students’ Performance - Vilo, Anna Marie Ewican; Taha, Hapifa Sakilan (Future Science / FSH-PH Publications, 2023)
The study was conducted to assess the effectiveness of Blended Learning Approach (BLA) and its implication on the students’ performance. The study utilized the descriptive-evaluative research design and it was conducted at Sultan Kudarat State University-Kalamansig Campus. Further, this study utilized simple random sampling to select the number of respondents. Twenty-three (23) teachers and twenty-nine (29) students during the 2nd semester, A.Y 2020-2021 were used as the respondents of the study. A researchers-made questionnaire was utilized to collect the data. The data were analysed using Statistical Package for the Social Sciences (SPSS) Software V21 x64. Statistical tools used were the frequency and percentages counts, mean, and grand mean. The Pearson-Product moment correlation coefficient was also utilized. The level of effectiveness of blended learning approach was fairly effective as assessed by both teachers and students. The students’ performance was described as above average. Further, the effectiveness on the use of blended learning approach has a significant relationship with the students’ performance. It is recommended that that the teachers’ expertise in using the said approach is indispensable. Thus, the SKSU-Kalamansig campus must maintain if not improve their performance in using the blended learning approach in various field of disciplines. Further, the institution must design a monitoring strategy relative on the use of blended learning approach for the sustainability of its effectiveness in developing students’ performance.